PENGEMBANGAN MODEL PENCARIAN KAMAR DALAM SISTEM RESERVASI HOTEL DENGAN ANTARMUKA BAHASA ALAMI - Hernawan Sulistyanto; Nurgiyatna - (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2015)
The modeling for Hotel occupancy representation will be complex problem because the presentation has linked with the other process, such as; arrival reservation, cancelation, length of stay, no-show, group reservation, seasonality and so on. Therefore, in brief, the appearing problems that are rise up now is not on limiting workers or capital, but more to providing information in reservation management. Information assessing should give facility by providing integral from data reservation of many information sources through hotels link. Stepping from this problem, so there is recommendation of providing the software for reservation systems based on natural language processing. The existing of natural language processing based reservation by hoping to manage guest candidate placement process at the room of hotel as in line with their own preferences.Keywords: hotel room, natural language processing, reservation